1967
DOI: 10.1161/01.res.21.6.833
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Vascular Leakage Caused by Histamine-Type Mediators

Abstract: A current hypothesis maintains that the vascular leakage induced by histamine, serotonin, and bradykinin is brought about by a hydrostatic mechanism: The larger veins are said to contract; the venules are therefore submitted to an increase in pressure, which causes their wall to give way. To test this hypothesis, vessels of an exposed striated muscle (rat and rabbit cremaster) were photographed while treated with the above-mentioned substances; the occurrence of vascular leakage was tested by the intravenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(75 citation statements)
references
References 15 publications
3
72
0
Order By: Relevance
“…20 ' 40 By the fura-2 assay, we found a basal level of 0.11 ±0.05 fiM calcium ions in the endothelial cells. After addition of histamine, an immediate increase in cytoplasmic calcium concentration was observed, as detected fluorimetrically by an increase in fluorescence at excitation 340 nm and emission at 510 nm ( Figure 5A).…”
Section: Effect Of Vasoactlve Substances On Cytoplasmic Calcium Concementioning
confidence: 77%
See 2 more Smart Citations
“…20 ' 40 By the fura-2 assay, we found a basal level of 0.11 ±0.05 fiM calcium ions in the endothelial cells. After addition of histamine, an immediate increase in cytoplasmic calcium concentration was observed, as detected fluorimetrically by an increase in fluorescence at excitation 340 nm and emission at 510 nm ( Figure 5A).…”
Section: Effect Of Vasoactlve Substances On Cytoplasmic Calcium Concementioning
confidence: 77%
“…The unexpected finding that histamine increases the passage of macromolecules through monolayers of cultured endothelial cells of human aorta and carotid artery may suggest this, but it may also reflect an in vitro activation of these cells. From in vivo experiments, Majno et al 20 postulated that histamine acted on a contractile mechanism of rat and rabbit venule endothelial cells. In favor of this, Rotrosen et al 84 demonstrated an increase in cytoplasmatjc calcium concentration after stimulation of suspended human umbilical vein endothelial cells, which coincided with a change in F-actin content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine released from nerve terminals, transiently 'opens' BBB (Abbott, 2000). It has been shown that histamine increases vascular permeability via contraction of ECs (Majno et al, 1967) and increases formation of pinocytotic vesicles in ECs (Gross et al, 1982). Thus, histamine affects both transcellular and paracellular pathways, and as such was an appropriate tool in the study.…”
Section: Discussionmentioning
confidence: 99%
“…VENULAR LEAKAGE : As shown by Majno et al (24)(25)(26) the topical or systemic administration of histamine is followed by vascular leakage characteristically restricted to venules . The capability of HF to induce a histammelike effect was assessed through two lines of experiments testing: (a) HF monomers' capability to induce the extravasation of previously injected carbon black particles, and (b) extravasation at the level of venules of some of the intravascularly administered HF aggregates (HFa).…”
mentioning
confidence: 99%